Plexin B1 controls Treg numbers, limits allergic airway inflammation, and regulates mucins - Chapoval, Svetlana P.; Gao, Hongjuan; Fanaroff, Rachel; Keegan, Achsah D. (Frontiers in Immunology, 2024)
We investigated the effect of global Plexin B1 deficiency on allergic airway responses to house dust mite (HDM) or ovalbumin (OVA). In the HDM model, there were higher Th2 cytokine levels in the BALF of Plexin B1 knock-out (KO) mice compared to wild type (WT), and tissue inflammation and mucus production were modestly enhanced. In the OVA model, Plexin B1 deficiency led to increases in lung inflammation, mucus production, and lung Th2 cytokines accompanied by dysregulated mucin gene expression without affecting anti-OVA IgE/IgG1 levels. Spleen cells from Plexin B1 KO mice proliferated more robustly than WT cells in vitro to a variety of stimuli. Plexin B1 KO CD4+ T cells from spleens expressed higher levels of Ki-67 and CD69 compared to WT cells. Spleen cells from naïve Plexin B1 KO mice secreted increased amounts of IL-4 and IL-6 when pulsed in vitro with OVA whereas in vivo OVA-primed spleen cells produced IL-4/IL-5 when subjected to in vitro OVA restimulation. The upregulated allergic inflammatory response in Plexin B1 KO mice was associated with a lower number of Tregs in the lung tissues. Moreover, these mice displayed lower numbers of Treg cells in the lymphoid tissues at the baseline. These results demonstrate a previously unrecognized link between Plexin B1, Treg cells, and mucus in allergic lung inflammation.